Incarnation theology versus the sacralisation of authority - Müller, Retief (HTS teologiese studies, 2015)
This article juxtaposed the theological theme of incarnation with quasi-religious invasions of public power structures and institutions in southern Africa, which has been described by the term sacralisation of authority. Incarnational theology as constructed on the model of the Incarnation of Jesus Christ concerns a Divine-human border crossing from above to below or from power into powerlessness. Sacralisation of authority concerns an opposite process whereby mundane structures and people of power seek to bolster their authority even further by the acquisition of godlike attributes. This article referred to political realities in southern Africa, particularly in Zimbabwe and South Africa as illustrative of the latter, whereas the Tshwane Leadership Foundation – a non-governmental organisation (NGO) operating in Tshwane’s inner city – served as a case study in incarnational theology of the grassroots.